A study of the deposition and distribution of copper alloy vessels in Roman Britain - Lundock, Jason (Archaeopress Roman archaeology, 2015)
This work collects together data concerning copper alloy vessels from Roman Britain and relates this evidence to prevailing theories of consumption, identity and culture change in Britain during this time. The aims of this study are to collect a catalogue of copper alloy vessels from England and Wales, categorise them by form, typology, context, chronology and geographic distribution, offer interpretations concerning their cultural associations, manners of consumption, functionality and development over time before commenting upon their value as small finds material reflective of culture change more broadly within Britain during the Roman period